A 3nm-thick, quasi-single crystalline Cu layer with ultralow optoelectrical losses and exceptional durability. (15th January 2022) - Jeong, Eunwook; Ikoma, Yoshifumi; Lee, Taehyeong; Kim, Hyejin; Yu, Seung Min; Lee, Sang-Geul; Bae, Jong-Seong; Han, Seung Zeon; Lee, Gun-Hwan; Choi, Dooho; Choi, Eun-Ae; Yun, Jungheum
Abstract: An ultrathin, highly crystalline, two-dimensional Cu layer is necessary for simultaneously achieving ultralow electrical and optical losses in transparent electrodes. However, perfect Cu wetting on heterogeneous oxide substrates has not yet been achieved. Herein, we report the Ge-mediated fabrication of an ultrathin, highly crystalline, complexly continuous Cu layer. The unique surfactant-like segregation of atomic Ge towards the outermost boundaries of the Cu geometries remarkably enhanced Cu wetting on the ZnO substrate. Numerical simulation indicated that the enhanced wetting can be attributed to the simultaneous decreases in the thermodynamic cohesive and formation energies at the surface and interface of the Cu nanostructures owing to Ge segregation. This enabled the fabrication of an ultrathin (∼3 nm), highly crystalline, two-dimensional Cu layer in a ZnO/Cu/ZnO configuration, which exhibited a record-low average optical loss at a near-bulk resistivity (8 × 10 −8 Ω m) comparable to those of conventional Ag electrodes; it also showed exceptional durability in water, ozone, and high-temperature (up to 400 °C) environments. These unique features would ensure the development of highly reliable optoelectrical devices employing Cu superstructure-based transparent electrodes as inexpensive alternatives to Ag-based transparent electrodes. Graphical abstract: Experimental and numerical insights into the Ge-mediated Cu epitaxy on ZnO substrates are provided for the fabrication of a 3 nm-thick, quasi-single crystalline Cu layer simultaneously exhibiting ultralow optoelectrical losses and high stability against corrosion and thermal loading. Image, graphical abstract